APORTE DE LAQUÍMICA ANALÍTICA A LA FORMACIÓN CIENTÍFICA DE LOS PROFESORES DE QUÍMICA - Franco Ruiz, Carlos Arturo; Salcedo Torres, Luis Enrique (Tecné, Episteme y Didaxis: TED, 2000)
ln this work it presented the results obtained when experiencing to pedagogic strategy based on the resolution of problems in Analytic Chemistry with the propose of contributing to the scientific formation of future professors of chemistry Evolution is presented in the conceptions of Science, investigation and scientific work, as well as in the key aspects of the resolution of analytic problems: hypothesis emission, design of experiments, identification of the analytic problems, handling information. They don’t advance significantly in the delimitation of the field of validity of results.